The Demand for Teacher Characteristics in the Market for Child Care: Evidence from a Field Experiment - Casey Boyd-Swan; Chris M. Herbst (Institute of Labor Economics (IZA), 2017)
Many preschool-age children in the U.S. attend center-based child care programs that are of low quality. This paper examines the extent to which teacher qualifications widely considered important inputs to classroom quality are valued by providers during the hiring process. To do so, we administered a resume audit study in which job-seeker characteristics were randomly assigned to a large number of resumes that were submitted in response to real child care job postings in 14 cities. Our results indicate that center-based providers may not hire the most qualified applicants. For example, we find that although providers have a strong preference for individuals with previous work experience in early childhood education (ECE), those with more ECE experience are less likely to receive an interview than those with less experience. We also find that individuals with bachelor's degrees in ECE are no more likely to receive an interview than their counterparts at the associate's level, even in the market for lead preschool-age teachers. Furthermore, those revealing high levels of academic performance, as measured by grade point average, are generally not preferred by child care providers. Finally, it appears that some non-quality attributes do not influence hiring decisions (e.g., signaling car ownership), while others have large effects on teacher hiring (e.g., applicant race/ethnicity). Together, our findings shed light on the complex trade-offs made by center-based providers attempting to offer high-quality programs while earning sufficient revenue to stay in business.
Keywords: I20; J23; J24; J71; 330; child care quality; teacher qualifications; resume audit study; field experiment